2020
DOI: 10.1007/s00018-020-03571-2
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-Bs enhance their GAP activity with a novel activation switch loop generating a cooperative enzyme

Abstract: Plexins receive guidance cues from semaphorin ligands and transmit their signal through the plasma membrane. This family of proteins is unique amongst single-pass transmembrane receptors as their intracellular regions interact directly with several small GTPases, which regulate cytoskeletal dynamics and cell adhesion. Here, we characterize the GTPase Activating Protein (GAP) function of Plexin-B1 and find that a cooperative GAP activity towards the substrate GTPase, Rap1b, is associated with the N-terminal Jux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Moreover, our conclusion concerns mostly inter-domain interactions and thus is less likely to be sensitive to the structural details, as the main driving force is the electrostatic interactions between the GTPases and membrane (Figure 3G), rather than any specific residue-residue interactions arising from a specific conformation. Reassuringly, our findings are supported by a recent study on plexin B1, which (Li et al, 2020) identified the functional importance of the buttress segment (or "activation switch loop" as is referred therein) based on analysis of plexin enzymatic turnover, and showed that the segment helps stabilize the dimerization helix when the plexin active site is occupied by Rap.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, our conclusion concerns mostly inter-domain interactions and thus is less likely to be sensitive to the structural details, as the main driving force is the electrostatic interactions between the GTPases and membrane (Figure 3G), rather than any specific residue-residue interactions arising from a specific conformation. Reassuringly, our findings are supported by a recent study on plexin B1, which (Li et al, 2020) identified the functional importance of the buttress segment (or "activation switch loop" as is referred therein) based on analysis of plexin enzymatic turnover, and showed that the segment helps stabilize the dimerization helix when the plexin active site is occupied by Rap.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, our conclusion is not sensitive to the fine structures, as the main driving force is the electrostatic interactions from the interface between the GTPases and membrane (Figure 3F), rather than any specific residue-residue interactions arising from a specific conformation. Reassuringly, our findings are supported by a recent study on plexin B1, which (Li et al, 2020) identified the functional importance of the buttress segment (or “activation switch loop” as is referred therein) based on analysis of plexin enzymatic turnover, and showed that the segment helps stabilizing the dimerization helix when the plexin active site is occupied by Rap.…”
Section: Discussionsupporting
confidence: 85%
“…For example, deletion of the plexin A1 sema domain converts the protein from an autoinhibited form to a constitutively active protein (in the absence of ligand) ( 47 ). In principle, it is possible that plexin D1 may undergo an inactive to active state transition without the need for homodimerization ( 7 , 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…47 In principle, it is possible that Plexin D1 may undergo an inactive to active state transition without the need for homodimerization. 7,[63][64] The receptors examined here do not form heterotypic interactions in the absence of ligand, except for Plexin A2 and Plexin A4. The class A plexins have conserved residues which may contribute to heterodimerization; however, these interactions had not been reported prior to the present study.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%